Propofol: Relation between Brain Concentrations, Electroencephalogram, Middle Cerebral Artery Blood Flow Velocity, and Cerebral Oxygen Extraction during Induction of Anesthesia - Ludbrook, Guy L.; Visco, Elizabeth; Lam, Arthur M. (Anesthesiology (Philadelphia), 2002)
The potential benefit of propofol dose regimens that use physiologic pharmacokinetic modeling to target the brain has been demonstrated in animals, but no data are available on the rate of propofol distribution to the brain in humans. This study measured the brain uptake of propofol in humans and the simultaneous effects on electroencephalography, cerebral blood flow velocity (V(mca)), and cerebral oxygen extraction. Seven subjects had arterial and jugular bulb catheters placed before induction. Electroencephalography and V(mca) were recorded during induction with propofol while blood samples were taken from both catheters for later propofol analysis. Brain uptake of propofol was calculated using mass balance principles, with effect compartment modeling used to quantitate the rate of uptake. Bispectral index (electroencephalogram) values decreased to a minimum value of approximately 4 at around 7 min from the onset of propofol administration and then slowly recovered. This was accompanied by decreases in V(mca), reaching a minimum value of approximately 40% of baseline. Cerebral oxygen extraction did not change, suggesting parallel changes in cerebral metabolism. There was slow equilibrium of propofol between the blood and the brain (t(1/2keo) of 6.5 min), with a close relation between brain concentrations and bispectral index, although with considerable interpatient variability. The majority of the decreases in V(mca), and presumably cerebral metabolism, corresponded with bispectral index values reaching 40-50 and the onset of burst suppression. Description of brain distribution of propofol will allow development of physiologic pharmacokinetic models for propofol and evaluation of dose regimens that target the brain.